A Clinical Case of Breast Reconstruction with Greater Omentum Flap for Treatment of Upper Extremity Lymphedema. Issue 9 (September 2019) - Sinelnikov, Mikhail Y.; Chen, Kuo; Sukorceva, Natalia S.; Lan, Mu; Bikov, Igor I.; Zakirova, Albina A.; Reshetov, Igor V.
Abstract : Summary: Patients presenting with complications regarding breast cancer surgery require individualized surgical protocol for correction and reconstruction. This clinical case summarizes our clinical experience in the application of the free greater omentum flap for treatment of upper extremity lymphedema and breast reconstruction. This method combines aesthetic reconstruction of the breast with functional correction. The presented clinical vignette features a patient with post-biquadrantectomy upper extremity lymphedema. A free greater omentum flap was chosen for the purpose of breast reconstruction and vascularized lymph node transfer to treat upper extremity lymphedema. Upper extremity circumferences were monitored before and after surgical correction. The revascularized flap survived well after the operation and the reconstructed breast had a natural appearance. Six months after the operation, the patient's upper extremity circumferences decreased significantly, and the pain and swelling were also alleviated. The patient was satisfied with the results. The use of the free greater omentum flap for breast reconstruction and treatment of upper extremity lymphedema provides both aesthetic and functional patient rehabilitation. The application of this technique requires proper patient selection and thorough surgical planning.